Type 2 diabetes in youth: A phenotype of poor cardiorespiratory fitness and low physical activity - Shaibi, Gabriel Q. (2009)
OBJECTIVE: The increased incidence of obesity and type 2 diabetes (T2D) among youth has prompted the development of guidelines for healthy cardiorespiratory fitness (CRF) and physical activity (PA) levels in the pediatric population. It is unclear whether youth with T2D meet these guidelines as previous research has not included type 2 diabetics. Therefore, the purpose of this investigation was to examine CRF and PA in youth with T2D and compare these results with recently published normative data for CRF and guidelines for PA in youth. METHODS: Forty adolescents (17 males and 23 females) with T2D were assessed for moderate-to-vigorous PA via the 7-day PA recall. CRF was determined by a progressive cycle ergometer test and indirect calorimetry. PA levels were compared with recently published guidelines for youth of 60 minutes per day, and CRF data were compared with age- and sex-adjusted normative values from the National Health and Nutrition Examination Survey 1999–2002. RESULTS: Only 17.6% (3/17) of boys and 21.7% (5/23) of girls met PA guidelines, while none of the participants met criteria for healthy CRF. When compared with normative CRF data for US youth, ~93% of boys and 95% of girls scored below the 10th percentile. CONCLUSIONS: These results suggest that youth with T2D exhibit low levels of CRF and the majority do not participate in recommended amounts of PA. Practitioners working with type 2 diabetic youth need to emphasize the importance of regular PA to increase CRF and promote cardiovascular health in an effort to decrease long-term diabetes-related complications.